Interface reinforcement and a new characterization method for pore structure of pervious concrete. (18th January 2021) - Ni, Tongyuan; Ma, Wenbin; Yang, Yang; Yu, Jingru; Liu, Jintao; Jiang, Chenhui; Gu, Chunping
Highlights: Interface of pervious concrete (PC) was reinforced with silica fume and fly ash. The interface enhancement of PC was characterized by the micro hardness. Pore characterization of PC based on slice image (PSI) was proposed. Feasibility and accuracy of PSI method was compared with CT scanning method. Abstract: Pervious concrete (PC) is utilized in pavement engineering as a kind of environment-friendly material, but its application is limited to some extent since the contradiction between strength and permeability is not easy to be compromised. In this paper, interface transition zone (ITZ) of PC was enhanced using silica fume (SF), fly ash (FA) and dispersible latex powder (DLP). The interface reinforcement effect was characterized by micro hardness of ITZ. In order to correlate pore structure of PC to its permeability, a new method based on slice image (PSI) was proposed. The micro hardness tests results indicated that the compactness of ITZ in PC had been improved with SF and FA, and the bonding strength between matrix and aggregate could be elevated. The proposed method was proved to be feasible and accurate in terms of the observation that the porosity measured through the method coincided with that obtained from the frequently-used CT scanning method.